Combinatorial actions of IL-22 and IL-17 drive optimal immunity to oral candidiasis through SPRRs. - Felix E Y Aggor; Martinna Bertolini; Bianca M Coleman; Tiffany C Taylor; Nicole O Ponde; Sarah L Gaffen (PLoS Pathogens)
Oropharyngeal candidiasis (OPC) is the most common human fungal infection, arising typically from T cell immune impairments. IL-17 and IL-22 contribute individually to OPC responses, but here we demonstrate that the combined actions of both cytokines are essential for resistance to OPC. Mice lacking IL-17RA and IL-22RA1 exhibited high fungal loads in esophagus- and intestinal tract, severe weight loss, and symptoms of colitis. Ultimately, mice succumbed to infection. Dual loss of IL-17RA and IL-22RA impaired expression of small proline rich proteins (SPRRs), a class of antimicrobial effectors not previously linked to fungal immunity. Sprr2a1 exhibited direct candidacidal activity in vitro, and Sprr1-3a-/- mice were susceptible to OPC. Thus, cooperative actions of Type 17 cytokines mediate oral mucosal anti-Candida defenses and reveal a role for SPRRs.